WHATSAPP ԲՋՋԱՅԻՆ ՀԱՎԵԼՎԱԾԻ ՕԳՏԱԳՈՐԾՈՒՄԸ ՕՏԱՐ ԼԵԶՈՒՆԵՐԻ ԴԱՍԱՎԱՆԴՄԱՆ ՄԵՋ - Ovchinnikova, Maya; Plaksina, Nataliya (Օտար լեզուները մասնագիտական նպատակների համար, 2023)
The article is devoted to the use of the WhatsApp mobile application in the process of learning a foreign language in order to form and improve the communicative language competence of students. This study aims at examining the effectiveness of WhatsApp usage in developing language skills while teaching foreign languages.The article discusses the advantages and disadvantages of using this resource in the practice of teaching a foreign language as it has become one of the most famous messengers used around the world thanks to its capabilities which should undoubtedly be used to teach certain aspects of learning a foreign language. Work plan for the WhatsApp application usage when learning a foreign language in a student audience is suggested.The methodology of work on the development of all types of speech activity including language exercises for the development of reding, listening, writing and speaking skills by means of the WhatsApp mobile application is proposed.